A mental health survey among young front-line clinicians in high-risk areas during the COVID-19 sporadic epidemic in China - Suo, Xingbo; Zhang, Yang; Liu, Qingxia; Zhao, Gaofeng; Zhu, Yanan; Liu, Yan; Zhai, Jinguo (Frontiers in Psychiatry, 2022)
Background: The sporadic coronavirus disease (COVID-19) epidemic has placed enormous psychological stress on people, especially clinicians. The objective of this study was to examine depression, anxiety, quality of life (QOL), and related social psychological factors among young front-line clinicians in high-risk areas during the COVID-19 sporadic epidemic in China and to provide a reference for formulating reasonable countermeasures. Methods: In this cross-sectional study, demographic information, COVID-19-related questions, anxiety (Generalized Anxiety Disorder-7, GAD-7), depression (Patient Health Questionnaire-9, PHQ-9), insomnia (Insomnia Severity Index, ISI), stress (Perceived Stress Scale-10, PSS-10), and QOL (World Health Organization Quality of Life-brief version, WHOQOL-BREF) were collected. Binary logistic regression analysis was used to test the relationships between anxiety and/or depression and other related problems. Multiple linear regression analysis was used to test the relationships among factors influencing QOL. Results: A total of 146 young front-line clinicians were included. The prevalence rates of depression, anxiety, and anxiety-depression comorbidity were 37.7% (95% CI=29.7 to 45.6%), 26.0% (95% CI=18.8 to 33.2%), and 24.0% (95% CI=17.0 to 31.0%), respectively. Severe stress (OR=1.258, 95% CI=1.098 to 1.442, P<0.01) and insomnia (OR=1.282, 95% CI=1.135 to 1.447, P<0.01) were positively correlated with depression. Severe stress (OR=1.487, 95% CI=1.213 to 1.823, P<0.01) and insomnia (OR=1.131, 95% CI=1.003 to 1.274, P<0.05) were positively correlated with anxiety. Severe stress (OR=1.532, 95% CI=1.228 to 1.912, P<0.01) was positively correlated with anxiety-depression comorbidity. However, insomnia (OR=1.081, 95% CI=0.963 to 1.214, P>0.05) was not correlated with anxiety-depression comorbidity. The belief that the vaccine will stop the COVID-19 pandemic (OR=0.099, 95% CI=0.014 to0.715, P<0.05) was negatively correlated with anxiety and anxiety-depression comorbidity (OR=0.101, 95% CI=0.014 to 0.744, P<0.05). Severe stress (B=-0.068, 95% CI=-0.129 to -0.007, P<0.05) and insomnia (B=-0.127, 95% CI=-0.188 to -0.067, P<0.01) were negatively correlated with QOL. The belief that the vaccine could provide protection (B=1.442, 95%CI=0.253 to 2.631, P<0.05) was positively correlated with QOL. Conclusions: The prevalence of depression, anxiety, and even anxiety-depression comorbidity was high among young front-line clinicians in high-risk areas during the COVID-19 sporadic epidemic in China. Various biological and psychological factors as well as COVID-19-related factors were associated with mental health issues and QOL.